2020
DOI: 10.1108/ijaim-01-2020-0002
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of IFRS using innovation diffusion models

Abstract: Purpose This study aims to examine the diffusion pattern of International Financial Reporting Standards (IFRS) into the countries and identifies the channels of diffusion. Design/methodology/approach Data includes 98 countries that made a public commitment to IFRS adoption from 2000 to 2016. Adoptee countries are categorized based on Rogers’ adopter categorizations to understand country characteristics. Innovation diffusion models such as internal influence, external influence and bass diffusion that explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Very few studies have used the DOI theory to illustrate the relevant benefits or effects of IFRS adoption (Dayyala et al, 2020;El-Helaly et al, 2020;Elmghaamez, 2019). According to the DOI theory, adopters of innovations might experience desirable or undesirable outcomes, direct or indirect consequences, and expected or unexpected benefits due to the impact of their social factors This uncertainty of the outcomes could lead to either rejection or accepting such innovations (El-Helaly et al, 2020;Elmghaamez, Gerged, & Ntim, 2020;Oliveira & Santos, 2019;Rogers, 1995).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Very few studies have used the DOI theory to illustrate the relevant benefits or effects of IFRS adoption (Dayyala et al, 2020;El-Helaly et al, 2020;Elmghaamez, 2019). According to the DOI theory, adopters of innovations might experience desirable or undesirable outcomes, direct or indirect consequences, and expected or unexpected benefits due to the impact of their social factors This uncertainty of the outcomes could lead to either rejection or accepting such innovations (El-Helaly et al, 2020;Elmghaamez, Gerged, & Ntim, 2020;Oliveira & Santos, 2019;Rogers, 1995).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Theoretically, very few studies have employed the DOI theory, popularized by Rogers in 1962, to explain the global diffusion of IFRS (e.g., Dayyala, Zaidi, & Bagchi, 2020;El-Helaly et al, 2020;Elmghaamez, 2019). For instance, recent research conducted by El-Helaly et al (2020) employed DOI theory to explain how countrylevel control of corruption may hinder or expand IFRS adoption across non-European Union (EU) countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of IASB experts in Jordan ranked eighth with a mean of 3.1452. In this context, findings from Dayyala, Zaidi and Bagchi [76] revealed that collaboration among countries and IASB is one of the main factors that help in adopting and applying IFRS. Lack of active market in Jordan ranked ninth with a mean of 3.0968.…”
Section: Accounting Standards Implementation Challengesmentioning
confidence: 99%
“…Inferring from the studies of Kleinaltenkamp et al (2012) and Vargo et al (2020) all the actors involved in MCP are resource integrators who cocreate phenomenologically while MCP diffusion is a critical part of the innovation processes. Besides, Dayyala et al (2020) integrates innovation diffusion models based on internal, external and bass diffusion and founds that International Financial Reporting Standards (IFRS) diffusion is possible through external influence with vertical communication, through internal influence in respect of imitation and interpersonal communication across the borders. This result also established the dynamism and inclusiveness of innovation diffusion.…”
Section: Diffusion Of Innovation and Theory Of Domesticationmentioning
confidence: 99%